Application of lactobionic acid and nonionic surfactants as solubilizing agents for parenteral formulation of clarithromycin - Zakeri-Milani, Parvin (Tabriz University of Medical Sciences, 2012)
Purpose: The purpose of this paper is to enhance the solubility of clarithromycin (CLR) using nonionic surfactants and some type of acids for preparation of the new formulations. Methods: Myrj 52 and chremophor (2.5 and 5% w/v) were used in two concentrations. To investigate solubility, the formulations were shaken for 48 hours at room temperature. For stability test, lyophilized samples were maintained in refrigerator at 4° C, and in oven at 40° C. Drug analysis was performed by reverse phase high performance liquid chromatography (HPLC) with ultraviolet detection. Results: Solubility tests indicated that lactobionic acid was the most effective to increase clarithromycin solubility and chremophor showed higher enhancing effect than myrj 52 on CLR solubility. The stability tests results also confirmed that shelf-lives of all formulations have been the equivalent to 24 months. Conclusion: On the whole, formulations described in this article may be very suitable for industrial-scale manufacturing and clinical application.